2006
DOI: 10.1103/physrevlett.96.195004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of 2D Images of Temperature Fluctuations during Sawtooth Oscillation with Theoretical Models

Abstract: High temporal and spatial resolution two-dimensional (2D) images of electron temperature fluctuations were employed to study the sawtooth oscillation in the Toroidal Experiment for Technically Oriented Research tokamak plasmas. The 2D images are directly compared with the expected 2D patterns of the plasma pressure (or electron temperature) from various theoretical models. The observed experimental 2D images are only partially in agreement with the expected patterns from each model: The image of the initial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…On MST, Choi et al 17 found that small sawtooth events are linearly unstable and hence spontaneous, while larger events require a nonlinear mode coupling for the instability to grow. In sawtooth reconnection, detailed measurements by Park et al 7,18,19 and Munsat et al 20 from the TEXTOR tokamak found toroidally localization of the reconnection events, with reconnection starting at specific toroidal locations with both "good" and "bad" curvature. These observations show that the 2D theories may not capture the essential physics to describe the onset of spontaneous reconnection.…”
Section: Introductionmentioning
confidence: 96%
“…On MST, Choi et al 17 found that small sawtooth events are linearly unstable and hence spontaneous, while larger events require a nonlinear mode coupling for the instability to grow. In sawtooth reconnection, detailed measurements by Park et al 7,18,19 and Munsat et al 20 from the TEXTOR tokamak found toroidally localization of the reconnection events, with reconnection starting at specific toroidal locations with both "good" and "bad" curvature. These observations show that the 2D theories may not capture the essential physics to describe the onset of spontaneous reconnection.…”
Section: Introductionmentioning
confidence: 96%
“…These measurements, which take advantage of advances in electron cyclotron emission imaging [64,65,66], have shown that sawtooth onset is localized both toroidally and poloidally and that the temperature profile flattening is well-organized as opposed to stochastic [67]. The localization is observed even though the magnetic field geometry is mainly 2D.…”
Section: Reconnection In 3dmentioning
confidence: 99%
“…On MST, Choi et al [19] found that small sawtooth events are linearly unstable and hence spontaneous, while larger events require a nonlinear mode coupling for the instability to grow. In sawtooth reconnection, detailed measurements by Park et al [9,20,21] and Munsat et al [22] from the TEXTOR tokamak found toroidally localization of the reconnection events, with reconnection starting at specific toroidal locations with both "good" and "bad" curvature. These observations show that the 2D theories may not capture the essential physics to describe the onset of spontaneous reconnection.…”
Section: Introductionmentioning
confidence: 99%